The Effect of Fundamental Factors on Corporate Social Responsibility in Property and Real Estate Companies in ISSI 2016-2020 - Weri Mahendra (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2022)
This study aims to analyze the fundamental factors of property and real estate companies in 2016-2020 in the Indonesian sharia stock index (ISSI), which consists of liquidity (CR), profitability (ROA), company size (CR), leverage (DER) influential or whether or not to corporate social responsibility (CSR). In this study, panel data analysis was used to find the best model, namely the Common Effect Model (CEM), Fixed Effect Model (FEM), Random Effect Model (REM) with purposive sampling method in order to obtain data in accordance with predetermined categories with data originating from 15 selected property and real estate companies that report corporate social responsibility and financial summary in the annual report and sustainability report that have been registered with ISSI in the 2016-2020 period. The results of this study simultaneously show that all independent variables, namely firm size (SIZE), profitability (ROA), liquidity (CR), leverage (DER) have a significant influence on CSR. Meanwhile, partially the firm size variable has a positive and significant effect on CSR and the leverage, profitability and liquidity variables do not have a positive and significant effect on CSR.